The Signaling Power of Unexcused Absence from School. Issue 3 (May 2023) - Pyne, Jaymes; Grodsky, Eric; Vaade, Elizabeth; McCready, Bo; Camburn, Eric; Bradley, Dominique
State and national school accountability policies situate preventing chronic absenteeism on par with meeting state standardized test benchmarks. We question relying on school attendance as both a component of accountability policies and a means of enhancing equity in schools. Our research suggests out-of-school factors unrelated to missed instruction account for most of the associations between absences and test score achievement—with unexcused absences driving those associations. Excessive absences—and particularly unexcused absences—don't harm students mainly through missed instruction. Instead, they reflect out-of-school harms students endure that have produced inequalities for years—and will continue to do so even if students show up or parents call in.